Kingdom of shadows [large type] : a novel - Furst, Alan (G.K. Hall ; Chivers Press, 2001)
In spymaster Alan Furst's most electrifying thriller to date, Hungarian aristocrat Nicholas Morath -- a hugely charismatic hero -- becomes embroiled in a daring and perilous effort to halt the Nazi war machine in eastern Europe.